Hubungan Kompetensi Pedagogik Guru dengan Motivasi Belajar Siswa dalam Pembelajaran Agama Islam - Luthfi Kurniawan; Raihan Raihan (Universitas Indraprasta PGRI, 2026)
This study aims to examine the relationship between teacher pedagogical competence and student learning motivation in Islamic Religious Education (PAI) learning at SMPN 101 Palmerah, West Jakarta. This study uses a quantitative approach with a survey method, while the analysis is carried out by Correlation and Regression. The study population is all eighth grade students of SMPN 101 Palmerah, West Jakarta. The sample was taken randomly from the population. The instrument used is a questionnaire. The results of the data analysis indicate that there is a significant and positive relationship between teacher pedagogical competence (variable X) and student learning motivation (variable Y). This result is supported by a correlation coefficient value of 0.780 which is in the strong category. Furthermore, the coefficient of determination (R2) value of 0.608 indicates that teacher pedagogical competence contributes 60.8% to student learning motivation, while the rest (39.2%) is influenced by other factors outside the variables studied.